Et vaig donar ulls i vas mirar les tenebres d’Irene Solà: afinitat goiesca i intertextualitat amb Woolf, Rodoreda, Coll et al. - Iribarren, Teresa (Studia Romanica Posnaniensia, 2025)
The article examines the sophisticated intertextual operation of literary and religious syncretism carried out by Irene Solà in I gave you eyes and you looked towards darkness (2023). It highlights the correspondences between Witches’ sabbath (1823) by Goya and the text that inspired it, Auto de fe (1811, 1820) by Fernández de Moratín. The argument is made that Solà constructs a coven to celebrate female sexual pleasure and condemn patriarchal violence against witches. The analysis of seven hypotexts – New Testament as well as works by Jaume Roig, Goethe, Woolf, Víctor Català, Rodoreda, and Pep Coll – supports the claim that Solà distorts Woolf’s Mrs Dalloway to shape a feminist coven centred on a blasphemous transposition of Bernadette Soubirous.